2016
DOI: 10.1038/srep19069
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Transcriptome during Human Spermatogenesis: Predicting the Potential Key Genes Regulating Male Gametes Generation

Abstract: Many infertile men are the victims of spermatogenesis disorder. However, conventional clinical test could not provide efficient information on the causes of spermatogenesis disorder and guide the doctor how to treat it. More effective diagnosis and treating methods could be developed if the key genes that regulate spermatogenesis were determined. Many works have been done on animal models, while there are few works on human beings due to the limited sample resources. In current work, testis tissues were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 59 publications
(69 reference statements)
0
52
0
3
Order By: Relevance
“…For example, during human spermatogenesis, transcriptomic dynamics can help predict the potential key genes that regulate male gamete generation 4 ; in different boar breeds, transcriptome analyses revealed differences in the development of sexual function 5 and in yellow catfish, comparative transcriptome analyses highlighted differences in expressed genes and signalling pathways between XY and YY testes 6 . However, information related to spermatogenesis during the different developmental stages in teleosts is limited.…”
Section: Introductionmentioning
confidence: 99%
“…For example, during human spermatogenesis, transcriptomic dynamics can help predict the potential key genes that regulate male gamete generation 4 ; in different boar breeds, transcriptome analyses revealed differences in the development of sexual function 5 and in yellow catfish, comparative transcriptome analyses highlighted differences in expressed genes and signalling pathways between XY and YY testes 6 . However, information related to spermatogenesis during the different developmental stages in teleosts is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The coiled-coil domain of HOOK1 is involved in the interaction with RIMBP3, which is associated with the manchette in elongating and elongated spermatids 30. Our team has obtained the dynamic changes of transcriptome profile for different stages of human germ cells recently, and the upregulated expression of HOOK1 gene in spermatid stage also indicated that it might play a role during human spermiogenesis 31. A critical role of Hook1 in spermiogenesis was suggested by azh mouse model, in which the deletion of exons 10 and 11 in Hook1 gene caused dysfunction of the manchette and the abnormal spermatozoa production 16.…”
Section: Discussionmentioning
confidence: 85%
“…To accomplish the former, male germ cells express many specialized transcriptional, translational, and RNA-processing factors (Chalmel and Rolland, 2015; Eddy, 2002; Iguchi et al, 2006; Lee et al, 2009; Licatalosi, 2016; MacDonald and Grozdanov, 2017; MacDonald and McMahon, 2010; Zagore et al, 2015; Zhu et al, 2016). Notably, male germ cells express mRNAs that differ in their 3′ ends due to alternative polyadenylation (Huber et al, 2005; Li et al, 2016; Liu et al, 2007; McMahon et al, 2006; Wallace et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…There are two major developmental goals for sperm production: restructuring of gene expression to enable postnatal germ cell differentiation and compaction of the haploid genome into the sperm head. To accomplish the former, male germ cells express many specialized transcriptional, translational, and RNA-processing factors (Eddy, 2002;Iguchi et al, 2006;Lee et al, 2009;MacDonald & McMahon, 2010;Chalmel & Rolland, 2015;Zagore et al, 2015;Licatalosi, 2016;Zhu et al, 2016;MacDonald & Grozdanov, 2017). Notably, male germ cells express mRNAs that differ in their 3 0 ends due to alternative polyadenylation (Wallace et al, 1999;Huber et al, 2005;McMahon et al, 2006;Liu et al, 2007;Li et al, 2016).…”
Section: Introductionmentioning
confidence: 99%